PENDAMPINGAN UMKM DALAM RANGKA PEMBERDAYAAN EKONOMI MASYARAKAT DI SURABAYA - Yulia, Novie Noordiana Rachma; Mardiyanto, Totok; Artalia, Puput; Putro, Suryati Eko; Indriawati, Arlisa; Widodo, Agus Purbo; Sudarsono, Heri (Komunitas Manajemen Kompetitif, 2023)
MSMEs have a very big role in the national economy, so if many MSMEs go out of business, it is feared that this will have a big impact on the national economy. Even though it is full of challenges, the MSME sector still has hope and opportunities to increase its business scale. This opportunity is still open for MSME business actors who want to innovate products and design them with a technological touch. The management process includes several steps, namely: Planning, Organizing, Actuating, Controlling (POAC), these four things need to be implemented so that MSMEs can grow. When starting a business, what must be formulated is the vision, mission, and corporate values. For example, in creating a business the superior values ​​are business that is excellent, honest, trustworthy, and so on. Company values ​​are important because they will become the soul of the company. In making a business plan, the first thing we do is identify where we are, where we are going (goal), why we want to go there, and what we will achieve. These measurements are important. The point is what is the best way to achieve the goals. The method used in this mentoring activity was through a combination of material presentation activities and coaching clinics, which were held in a total of 16 meetings. The result of the activity is an output in the form of a business plan which includes the vision, mission, goals, and business model for the MSME partners targeted by the activity. Other results include new logo designs for several partners so that the appearance becomes fresher and more attractive.